Frontispiece: Asymmetric Catalysis in Liquid Confinement: Probing the Performance of Novel Chiral Rhodium–Diene Complexes in Microemulsions and Conventional Solvents. Issue 40 (17th July 2019) - Deimling, Max; Kirchhof, Manuel; Schwager, Barbara; Qawasmi, Yaseen; Savin, Alex; Mühlhäuser, Tina; Frey, Wolfgang; Claasen, Birgit; Baro, Angelika; Sottmann, Thomas; Laschat, Sabine
Abstract : Improved reaction rate and enantioselectivity of Rh‐catalyzed asymmetric 1, 2‐additions of phenylboroxine to N‐tosylimine was realized when the conventional solutions were replaced by microemulsions stabilized by hydrophilic sugar surfactants containing equal amounts of H2 O/KOH and toluene/reactants. The norbornadiene ligands on the catalyst differ in the substitution pattern and oxazolidinone unit. For more information, see the Full Paper by T. Sottmann, S. Laschat and co‐workers onpage 9464 ff.